Measurement of glycolytic rates in cell suspensions using a recording pH meter (Revista Española de Fisiología, 1976)
A method for measuring continuously glycolytic rates in cell suspensions, using a recording pH meter, is described. Under the described conditions the method is very exact, sensitive and reproducible. The method can be applied to different cells and different conditions of assay calibrating in each case the pH range, cell concentration range and the ratio of delta protons to delta lactic acid.